Off-Record Strategies In Spousal Conflict: Violation Of The Principle Of Cooperation And Its Implications - Ni Wayan Novi Wulandari; I Dewa Putu Wijana (LPPM Institut Pendidikan Nusantara Global, 2026)
This study analyzes Off-Record Strategies in the speech acts of married couples during conflict, based on dialogue from the film